Concept of Education and Teaching from Ki Hajar Dewantara Point of View - Ummal Khoiriyah; Risma Amin; Zakaria Bintang Pamungkas (Hikamatzu | Journal of Multidisciplinary, 2026)
This study explores Ki Hadjar Dewantara’s concept of education and teaching as a foundational indigenous educational philosophy grounded in humanistic and cultural values. Employing a systematic literature review, the study synthesizes classical and contemporary scholarly works to examine the philosophical foundations, pedagogical principles, and contemporary relevance of Dewantara’s educational thought, with particular emphasis on the among system. The findings reveal that Dewantara conceptualized education as a process of humanization (memanusiakan manusia), aimed at fostering learner independence (kemerdekaan), moral character, and social responsibility through the balanced development of cipta (intellect), rasa (emotion), and karsa (will). Central to this framework, the among system positions teachers as guides, role models, and moral companions who facilitate learning through example, encouragement, and supportive supervision rather than coercion. The study further demonstrates that Dewantara’s ideas remain highly relevant in addressing contemporary educational challenges, including over-standardization, moral decline, and cultural alienation, offering a culturally responsive alternative to neoliberal and exam-oriented educational paradigms. Overall, this research affirms that Ki Hadjar Dewantara’s educational philosophy constitutes a comprehensive, ethical, and adaptable framework that continues to contribute meaningfully to debates on character education, learner-centered pedagogy, and the integration of local wisdom in modern education.